Internacionalização dos Programas de Pós-Graduação em Administração no Brasil no contexto do trabalho dos docentes pesquisadores - Costa Filho, Francisco Cenildo da (2021)
The aim of this study is to analyze the internationalization of Postgraduate Programs in Administration in Brazil in the context of the work of research professors. This is a research with a qualitative approach, analyzing the Programs with concepts 6 and 7 of CAPES, in the time frame of the 20172020 Quadrennium, thus evaluated for demonstrating indicators of a consolidated international insertion. The researched population belongs to the same group, with coordinators and research professors being privileged in programs with strong international insertion, to which semistructured interviews were applied. Thus, a bibliographic, documentary and field investigation was carried out, allowing for a triangulation of different sources, in order to ensure greater validity and reliability of the results. Qualitative content analysis was the chosen analysis technique for the treatment of the researched materials. The actions present in the Proposals of Postgraduate Programs in Administration, grades 6 and 7 of CAPES reveal the strong role of the researcher professor in this internationalization process. The study revealed that the institutional policy of internationalization is for some programs the origin of their international configuration, for others it is the nutrient that consolidates them in this process and for all of them, it is essential for maintaining the level of PPG excellence in Brazil. The internationalization process, however, has a strong concentration on the researcher professor. It is their individual initiatives, especially the relationship networks they have built, that consolidate opportunities to participate in research with international partners. Thus, the dynamics of this process makes the professor responsible for internationalizing the programs in which he works and is also burdened with the responsibility to finance some of the initiatives inherent in this process. The imperative of internationalization entails certain requirements for Brazilian research professors, such as mobility and the need to participate in international events, with impacts on the context of the professors’ personal and professional lives. It is clear, therefore, in the researchers’ speech, that the phenomenon of internationalization reproduces the rationality of hegemony of knowledge produced by the Global North, in which boundary zones are defined for intellectual work, according to the power relations that are established in the context of dispute for insertion on that border.